Morphemic analysis increases vocabulary and improves comprehension - Jarad, Najib Ismail (Glottodidactica, 2015)
The present study explored the effects of explicit and systematic teaching of morphemic analysis on vocabulary learning and comprehension. The reading class taught by the researcher was purposely taught the most common (30) prefixes and the most common (30) roots. Following fourteen 50-minute lessons, students were tested on their ability to recall the meanings of words used to teach the morphemic analysis skills, to derive meanings for new words that contained taught morphemic elements, and to comprehend text containing new words. The results indicated that (a) there was an immediate and delayed effect of morphemic analysis for lesson words, and (b) there was evidence that a morphemic approach improved students’ vocabulary and, consequently, their comprehension. The findings of this study provide support for the implementation of a morphemic approach for vocabulary instruction.